On Pathology Laboratory Recruitment and Retention: Insights From the 16 Personalities Type Indicators. Issue 4 (17th March 2021) - Chiou, Paul Z; Mulder, Lotte; Jia, Yuane
Abstract: Objectives: The specific aims of the study are to analyze relationships between the personality traits of laboratory professionals and choice of profession and preferred work settings. Methods: Data from practicing laboratory professionals were collected via a web-based survey tool to gather information about personality types, choice of profession, and work setting preferences among medical laboratory professionals. Results: Results of the survey showed that INFJ (Introversion, Intuition, Feeling, Judging) is the most common medical laboratory personality type across the various laboratory work settings and that there are no significant differences between the practitioners' personality type and the choice of profession within pathology. The study revealed laboratorians from higher-volume laboratories were 1.2 times more likely to prefer Judging than lower-volume laboratories, and younger medical laboratory practitioners were 2.3 times more likely to gravitate toward Perceiving than their older counterparts. Conclusions: The results of this study shed light on how employers can build on the personality preferences of the laboratory workforce to improve personal job satisfaction and laboratory productivity, quality, and work culture. The research implications are useful for laboratory recruitment and retention.